Rez Metal : Inside the Navajo Nation Heavy Metal Scene - Soltani Stone, Ashkan; Zappia, Natale A. (Book collections on Project MUSE., 2020)
"Rez Metal showcases the sounds, images, and stories of Navajo heavy metal bands and Native heavy metalers while exploring the deep and life-affirming power of heavy metal music within Indian Country"--